The SAGE handbook of mentoring - Clutterbuck, David; Kochan, Frances K.; Lunsford, Laura Gail; Dominguez, Nora; Haddock-Millar, Julie (SAGE Publications Ltd, 2017)
The SAGE Handbook of Mentoring provides a scholarly, comprehensive and critical overview of mentoring theory, research and practice across the world. A team of internationally renowned and emerging contributors map out the key historical and contemporary research, before considering modern case study examples and future directions for the field. The chapters are organised into four parts: Part One: The Landscape of Mentoring Part Two: The Practice of Mentoring Part Three: The Context of Mentoring Part Four: Case Studies of Mentoring Around the Globe.- Resumé vydavatel